A Extensão Rural e a Diversificação Produtiva da Agricultura Familiar em Áreas de Cultivo de Tabaco no Rio Grande do Sul: o caso de Dom Feliciano-RS - Deponti, Cidonea Machado; Schneider, Sergio (Universidade Federal Rural do Rio de Janeiro, 2015)
The main objective of this article is to analyze the action of the rural extension in the process of productive diversification of the family agriculture in Dom Feliciano-RS. For so much, it was looked for to understand the different meanings attributed to the culture of the tobacco by the farmers and its different conceptions of productive diversification. It was used as technique of collection of data the participant observation and the application of 40 interviews with semi-structured script. It was ended that there is a paradox - the ones that more needs attendance technique are the ones that less acess the service. The action of the rural extension is still focus in the intervention, propitiating little interface relationships and of social mediation. The idea of a model production only-pattern and of intervention for such a several social reality is I fail, although the farmers have the fact in common of they be producing of tobacco, this homogeneity of productive culture doesn't imply, for consequence, a social homogeneity of the productive units and less still of the projects and of the desires of the members of the families.